Does aid mitigate external shocks? - Paul Collier; Benedikt Goderis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper investigates the role of aid in mitigating the adverse effects of commodity export price shocks on growth in commodity-dependent countries. Using a large crosscountry dataset, we find that negative shocks matter for short-term growth, while the ex ante risk of shocks does not seem to matter. We also find that both the level of aid and the flexibility of the exchange rate substantially lower the adverse growth effect of shocks. While the mitigating effect of aid is significant in both countries with pegs and countries with floats, the effect seems to be smaller for the latter, suggesting that aid and exchange rate flexibility are partly substitutes. We investigate whether aid has historically been targeted at shock-prone countries, but find no evidence that this is the case. This suggests that donors could increase aid effectiveness by redirecting aid towards countries with a high incidence of commodity export price shocks.
Keywords: F35; O13; O47; 330; aid; commodities; export; price shocks